Conversion of four-stroke engines to six-stroke engines using epicyclic gearing in camshaft modification - E. Arabacı; M. Akar (Mechanical Sciences)
In this study, a compact, single-cylinder, spark-ignition, four-stroke engine commonly used in power generators is converted into a six-stroke engine. This conversion employed the free-stroke Kelem model, one of the six-stroke engine approaches described in the literature, which required modifications only to the camshaft. Without modification to the original crankshaft gear, a fixed-ratio epicyclic gear was applied to the camshaft gear to achieve the necessary speed ratio between the crankshaft and camshaft. Following the verification of the engine's original camshaft dimensions, new cam profiles were designed using a two-circular-arc cam profile. The cam lobes and cam gear were manufactured and assembled separately. During the experiments, a resistive load bank with a capacity ranging from 400 to 4000 W was employed to load the power generator and assess the engine's performance parameters. Fuel consumption, oil temperature, and exhaust gas temperature were measured, from which thermal efficiency, specific fuel consumption, and fuel consumption per cycle were calculated. The results showed that oil temperature decreased by 3.1 %, exhaust gas temperature decreased by 15.4 %, and thermal efficiency increased by 15.8 %. However, fuel consumption per cycle in the six-stroke engine increased by 29.9 %, indicating a higher engine load demand to achieve the desired power output. This study uses the original dimensions and characteristics of the test engine as a reference. No further modifications were made apart from the camshaft adjustment. The experimental findings demonstrate that four-stroke engines can be successfully converted into six-stroke engines, achieving improved fuel economy at the expense of reduced power output. The implementation of an epicyclic gear system into the camshaft gear without any modification to the crankshaft gear, along with the experimental validation of the model's usability, distinguishes this study from the existing literature.